Robot Controlled Six Degree Freedom Camera - Rejus Kumar , Arun V; Francis Britto, A. Sagai (International Journal of Psychosocial Rehabilitation, 2019)
The Operational System for Inspection, Research, and Instrument Support (OSIRIS) is a remotely operated free-flying camera robot. Designed to fly in air, OSIRIS has full six-axis control and can serve as a test platform for several areas of research, including attitude control, path planning, inspection tasks, and human-robot interaction. Similar vehicles designed in the past used ducted fans and compressed air for propulsion. OSIRIS implements an alternative propulsion system, the centrifugal pump-jet propeller. Upon vehicle integration, the system was tested in a micro-gravity environment on board NASA’s KC-135 Weightless Wonder V, where it had uninhibited motion. The testing was done in conjunction with the Reduced Gravity Student Flight Opportunities Program at Johnson Space Center. These tests were used to measure the functionality and effectiveness of the propulsion system and to determine a preliminary characterization of the vehicle dynamics. Analysis demonstrated that the propulsion system can effectively run a space simulator vehicle in air in a microgravity environment.